1994
DOI: 10.1183/09031936.94.07050881
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the occurrence of airway hyperreactivity in the general population: the importance of atopy and airway calibre

Abstract: The factors that determine the occurrence of airway hyperreactivity in the general population are not clearly understood. This study was designed to assess the independent effects of age, atopy, smoking and airway calibre. In a random sample of 2,415 adults aged 18-70 yrs we measured reactivity to methacholine as the dose provoking a 20% fall (PD20) in one-second forced expiratory volume (FEV1), atopy as the mean skin wheal response to three common environmental allergens, and airway calibre as the baseline FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies have shown PEF and FEV 1 changes are poorly related during mild bronchoconstriction induced by different stimuli [56][57][58]. However, a reduction in airway caliber would result in a greater increase in airway resistance and consequently greater airflow limitation [58,59]. Several previous studies have shown that airflow limitation can be present with normal PEF variability [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown PEF and FEV 1 changes are poorly related during mild bronchoconstriction induced by different stimuli [56][57][58]. However, a reduction in airway caliber would result in a greater increase in airway resistance and consequently greater airflow limitation [58,59]. Several previous studies have shown that airflow limitation can be present with normal PEF variability [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Atopy 296 Atopic individuals are prone to increased BHR Gender 296 Boys among children and females among adults have more occurrence of BHR Lung function 296 Lower FEV 1 and ratio of FEV 1 /FVC have been shown to be associated with increased occurrence of BHR Ethinicity 297,298 Pollen threshold levels for symptoms are differential according to ethnicity Smoking 299 Smoking is associated with increased BHR and respiratory infections Respiratory infection [300][301][302] Respiratory tract is infiltrated with inflammatory cells, post infectious state is associated with increased BHR…”
Section: Host Factorsmentioning
confidence: 99%